Sarah plain & tall : the DVD collection [videorecording (DVD)] - Close, Glenn, 1947-; Walken, Christopher, 1943-; Randall, Lexi; Stein, Margaret Sophie; Palance, Jack, 1919-2006; MacLachlan, Patricia (Hallmark hall of fame, 1999)
"Sarah, Plain and Tall:" A mail-order bride from Maine travels to Kansas in 1910 to join a widower, Jacob Witting, and his two children. "Skylark:" The Witting family is tested first by drought and then by separation, as Sarah and the children are forced to leave their Kansas farm to join Sarah's aunts in Maine while Jacob remains behind to try to save their livelihood. "Sarah Plain and Tall: Winter's End:" Having abandoned his family decades ago, Jacob's father John returns to the farm to try to mend his relationship with his son.